DINAMIKA HAKIKAT PENDIDIKAN DAN KEBUDAYAAN: PERSPEKTIF INTERKONEKSI DAN DAMPAK BERSAMA - Rahayu, Yusnita; Fariz, Ilma Fauziana; Nulhakim, Lukman; Haryadi, Rudi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
Education and culture are two aspects that are closely related to each other and have a significant influence on each other. Both support each other and cannot be separated in shaping people's lives. Education has a strategic role in every cultured society. To maintain the sustainability of a culture, education can be used as a means to introduce, understand and appreciate the culture of a society to the younger generation. Vice versa, culture plays a role in shaping education for a society by providing values, beliefs and norms that form the basis of the educational objectives. Therefore, education cannot be separated from culture and society as the owner of that culture.